Cryptocurrency and Blockchain Technology - Corbet, Shaen; Urquhart, Andrew; Yarovaya, Larisa (Batten-Corbet-Lucey Handbooks in Alternative Investments ;, 2020)
This handbook will provide a comprehensive treatment of the gamut of issues and challenges that exist through the development of both cryptocurrencies and blockchain technology. This will not be confined to simply the investment potential within these new technological areas. We will examine the challenges in the regulatory, legal, taxation, accounting, modelling, ethical, macroeconomic impact and internationalization issues. Research on cryptocurrencies and blockchain technology has identified issues such as pricing abnormalities and bubble-like behavior, indicating that these new assets are highly speculative in nature, contain a growing number of legal abnormalities (such as the hacking of exchanges and broad theft of investor assets) and a growing number of significant regulatory issues. It is paramount that we investigate each of these issues in great detail to help to determine whether cryptocurrencies and blockchain technology merits consideration as a sustainable alternative investment asset. The handbook will be useful for specialist technical audiences such as legal, accounting and financial practices. It will also be beneficial for upper level masters and research students in economics, law, accounting, taxation, investment and portfolio management.